KONSTRUKSI MODEL TATA KELOLA MADRASAH BERBASIS GOOD GOVERNANCE DAN NILAI ISLAMI - Gama Pratama; Abu Lubaba; Toriko Toriko (Universitas Islam Bunga Bangsa Cirebon, 2022)
This study aims to construct a madrasah governance model integrating Good Governance principles and Islamic values as a framework for improving the quality of Islamic educational institutions in Indonesia. The urgency of this research stems from the persistent gap between normative governance standards and their actual application in madrasah environments, which are characterized by unique socio-religious dynamics. Through a systematic library research (studi pustaka) methodology, this study examined and synthesized relevant academic literature, policy documents, and empirical findings published over the last decade. Data were gathered from reputable national and international journals, as well as reference books in Islamic educational management. The analysis employed the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that an effective madrasah governance model must integrate five core dimensions: transparency, accountability, participation, rule of law, and responsiveness — each reinterpreted through the lens of Islamic values such as amanah, shura, adalah, and mas'uliyyah. This integrated model bridges the structural demands of modern governance with the spiritual foundations of Islamic education, offering a comprehensive and contextually sensitive framework.